Mismatch Repair Pathway, Genome Stability and Cancer - Pećina-Šlaus, Nives; Kafka, Anja; Salamon, Iva; Bukovac, Anja (Frontiers in Molecular Biosciences, 2020)
The acquisition of genomic instability is one of the key characteristics of cancer cell, and microsatellite instability (MSI) is an important segment of this phenomenon. This review aims to describe the mismatch DNA repair (MMR) system whose deficiency is responsible for MSI and discuss cellular roles of MMR genes. Malfunctioning of MMR repair pathway increases the mutational burden of specific cancers and is often involved in its etiology, sometimes as an influential bystander and sometimes as the main driving force. Detecting the presence of MSI has for a long time been an important part of clinical diagnostics, but has still not achieved its full potential. MSI blueprint of a certain tumor can be useful for precize grading, evaluation of cancer chance and prognosis and to help us explain how therapy-resistant cancers arise. Furthermore, evidence indicates that MSI is an important predictive biomarker for the application of immunotherapy.